1999
DOI: 10.1089/107999099313479
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha Upregulates Gene Expression of Aquaporin-5 in Human Parotid Glands

Abstract: Aquaporins are a family of homologous membrane proteins that function as highly selective water channels. Aquaporin-5 (AQP5) is uniquely present in lacrimal and salivary glands, where it accounts for normal tear and saliva production. We tested the hypothesis that orally administered human interferon-alpha (HuIFN-alpha) benefits persons with xerostomia by augmenting the production of AQP5 protein by parotid gland epithelium. Cells from three human parotid glands were cultured with and without human lymphoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 22 publications
(27 reference statements)
0
32
0
2
Order By: Relevance
“…In another study, human parotid gland tissue cultured in the presence of low doses of IFN alfa expressed augmented aquaporin-5 (AQP5) transcription and protein production (34). Consequently, the increased UWS flow seen following IFN alfa treatment may be due to an upregulation of AQP5, with highly selective water channel proteins reported to be abnormally distributed in lacrimal and salivary glands of Sjö gren's syndrome patients (35,36).…”
Section: Cummins Et Almentioning
confidence: 99%
“…In another study, human parotid gland tissue cultured in the presence of low doses of IFN alfa expressed augmented aquaporin-5 (AQP5) transcription and protein production (34). Consequently, the increased UWS flow seen following IFN alfa treatment may be due to an upregulation of AQP5, with highly selective water channel proteins reported to be abnormally distributed in lacrimal and salivary glands of Sjö gren's syndrome patients (35,36).…”
Section: Cummins Et Almentioning
confidence: 99%
“…The application resulted in decreased immune cell infiltration and increased secretory response. IFN-␣ may directly increase the density of aquaporin5 in salivary gland tissue by up-regulating the gene and the protein expression (Smith et al ., 1999). Antagonizing the effects of IFN-␥by IFN-␣ / ␤may indirectly alter the outcome of pathological changes in patients with SS, as we observed in NOD.IFN-␥ -/-mice.…”
Section: (Iv) Summarymentioning
confidence: 99%
“…Mechanisms that Lead to AQP-1 Down-Regulation Two principal mechanisms are likely to contribute to down-regulation of AQP-1 in pSS myoepithelial cells. First, studies on lung epithelium and parotid glands have demonstrated that cytokines can up-and downregulate the expression of AQP molecules (Smith et al, 1999;Towne et al, 2001), and cytokines are known to be produced in increased quantities by acinar cells and lymphocytes in pSS glands (Boumba et al, 1995;Fox et al, 1994;Grisius et al, 1997). Second, AQP-1 expression may be altered as a consequence of functional inhibition of cholinergic neurotransmission.…”
Section: Role Of Aqp-1 and Myoepithelial Cells In Exocrine Gland Funcmentioning
confidence: 99%